Association between obesity and lipid profile in children 10--12 years of age - Ruqoyatul Himah; Endy P. Prawirohartono; Madarina Julia (Paediatrica Indonesiana, 2008)
Background Worldwide prevalence of obesity in children hasbeen increasing. Together with dyslipidemia and hypertension,obesity is associated with higher risk of cardiovascular morbiditylater in life.Objective The aim of this study was to assess associationbetween obesity and occurrence of dyslipidemia in 10-12 yearsold children.Methods We performed a cross sectional study on 53 obese and53 non-obese children matched for age and gender in Yogyakarta.Obesity was defined as body mass index (BMI) at or above the95th percentile of the CDC 2000 reference. The levels of totalcholesterol, LDL-cholesterol, HDL-cholesterol and triglyceridewere measured. Dyslipidemia was defined as increased level oftotal cholesterol, LDL-cholesterol, triglyceride and decreasedlevel of HDL-cholesterol.Results Obese children had higher risk of increased level oftriglyseride, i.e. RR 2.6 (95% CI 1.6 to 4.4), P<O.OOl anddecreased level ofHDL-cholesterol, i.e. RR 17.8 (95%CI 14.0 to20.1), P=0.003. Overall, relative risk for dyslipidemia in obesechildren was 5.2 (95%CI 4.2 to 5.9), P=0.002, higher than innon-obese children.Conclusion Compared to non-obese children, obese children havehigher risk of dyslipidemia, particularly hypertriglyceridemia andhypo-HDL.